Evaluation of Agricultural Waste-Based Briquettes as an Alternative Biomass Fuel for Cooking in Uganda - Omino, Joseph Oteu; Nkambwe, Sarah - Kizza; Kasima, Junior Senyonga; Mpewo, Maxmillan; Agunyo, Miria Frances (East African Nature and Science Organization, 2024)
Wood fuel has been adopted as a feasible alternative to cooking energy sources in efforts to replace fossil fuels. However, the exorbitant use of wood fuel has raised concern as it is the major cause of forest cover loss in Uganda. Briquettes have been recommended as sources of cooking energy with potential to substitute wood fuel. Unfortunately, sawdust, a product of deforestation, is the primary material used in making briquettes in Uganda. This instead augments the problem of fuel-induced deforestation. Agricultural wastes could potentially be converted into briquetting materials for generation of cooking energy, although these are less studied in Uganda. Thus, this study established the potential of agricultural wastes as alternative briquetting materials for use in cooking. Four fuel types: charcoal from Mangifera indica, firewood of Eucalyptus grandis, carbonized and non-carbonized briquettes from agricultural wastes, all from within Mukono District were used for the study. Laboratory based experiments were used to determine the physico-chemical characteristics of the fuels. Data were analysed using R software, Ver. 4.2.3. Carbonised briquettes’ mean performance measures were higher than conventional fuels (p≤0.05) and non-carbonised briquettes. The amount of energy required to attain experimental boiling point of water was higher (p≤0.05) in conventional fuels and non-carbonised briquettes than in carbonised briquettes. Duration to boil 5 litres of water was least with the conventional fuel sources. All the fuel sources’ emissions exceeded the maximum range recommended for indoor carbon monoxide levels. However, the particulate matter emission was lower in carbonised briquettes and charcoal than the other fuel sources. Agricultural waste-based carbonised briquettes could effectively be used as an alternative cooking energy source in Uganda. The study recommends conducting cost-benefit analyses on the use of agricultural waste-based briquettes as cooking energy sources